Nonlinear complex generalized zakharov dynamical system inconformal sense utilizing new kudryashov method - Secer, Aydin; Bayram, Mustafa; Ozdemir, Neslihan; Onder, Ismail; Esen, Handenur; Cinar, Melih; Aydin, Huseyin (IOP Publishing Ltd, 2024)
We take into account the nonlinear complex generalized Zakharov dynamical system which models the spread of the Langmuir waves in ionized plasma, in the conformal sense in this manuscript. Fractional wave transformation is enforced to convert the nonlinear fractional system to a nonlinear ordinary differential equation system. The new Kudryashov method which was recently introduced and is an efficient method, is implemented to the presented equation to acquire analytical solutions. The required constraint conditions are offered to ensure the validity of the obtained solutions. To analyze the physical interpretations for some of the produced solutions, we illustrate some graphical representations. We derive the bright and singular solitons. Furthermore, 2D views of the behavior of the solitons are represented to investigate the effect of the values of the parameters in the proposed model and fractional parameters. Also, the modulation instability of the model is investigated to ensure the obtained results are stable.
Keywords: zakharov dynamical system; conformable derivative; sardar sub-equation method; analytical solution; TRAVELING-WAVE SOLUTIONS; MODULATION INSTABILITY; EQUATION; EVOLUTION; Physics